First record of fertile Caloplaca arcisproxima and designation of its epitype (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Caloplaca arcisproxima (Teloschistaceae, lichenized fungi) was described from sterile specimens. Subsequently, we collected fertile thalli of the species in the Crimean Peninsula (Ukraine) and we provide characters of apothecia as its additional identification. Although the species is usually distinguishable by the shape of its sorediate squamules, the fertile specimen possesses characters of apothecia and we designate it as the epitype of C. arcisproxima. Identification of the epitype was supported by its ITS nrDNA sequence.
Keywords: Caloplaca citrina group, epitype designation, lichen-forming fungi, nomenclature.